Clopidogrel-associated acute migratory arthritis following kidney-pancreas transplantation. - Muthusamy, A; Vaidya, A; Friend, P (2006)
Clopidogrel is a potent inhibitor of platelet aggregation and has been used as an alternative, or as an adjunct to aspirin in reducing the risk of thrombosis. A 34-year-old uremic type 1 male diabetic patient who underwent simultaneous kidney-pancreas transplantation was given clopidogrel as he was allergic to aspirin. He developed polyarthralgia one week later, followed in a few days by symmetrical migratory polyarthritis, which resolved completely on withdrawing the drug. The implications to clinical management in a transplant setting are discussed.